2014
DOI: 10.1177/1059840514557160
|View full text |Cite
|
Sign up to set email alerts
|

Communicating With School Nurses About Sexual Orientation and Sexual Health

Abstract: Black and Latino young men who have sex with men (YMSM) are at disproportionate risk for sexually transmitted diseases (STDs), including HIV. This study informs school-centered strategies for connecting YMSM to health services by describing their willingness, perceived safety, and experiences in talking to school staff about sexual health. Cross-sectional data were collected from black and Latino YMSM ages 13–19 through Web-based questionnaires (n=415) and interviews (n=32). School nurses were the staff member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 16 publications
(15 reference statements)
1
41
0
1
Order By: Relevance
“…School nurses have the potential to play an important role as a trusted adult knowledgeable about health risk factors. However, in a study of racial and ethnic men who have sex with men, participants reported feeling comfortable discussing sex with school nurses, but not their same sex attraction . School nurses should adopt best practices to promote their care as LGBT‐affirming, such as posting a nondiscrimination policy, displaying LGBT symbols (eg, rainbow flag), and tailoring intake forms (eg, adding gender identities beyond male and female)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School nurses have the potential to play an important role as a trusted adult knowledgeable about health risk factors. However, in a study of racial and ethnic men who have sex with men, participants reported feeling comfortable discussing sex with school nurses, but not their same sex attraction . School nurses should adopt best practices to promote their care as LGBT‐affirming, such as posting a nondiscrimination policy, displaying LGBT symbols (eg, rainbow flag), and tailoring intake forms (eg, adding gender identities beyond male and female)…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study of racial and ethnic men who have sex with men, participants reported feeling comfortable discussing sex with school nurses, but not their same sex attraction. 24 School nurses should adopt best practices to promote their care as LGBT-affirming, such as posting a nondiscrimination policy, displaying…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we specifically focus on measures related to HIV and STD testing including demographics, sexual orientation, HIV/STD testing in the past year, testing venues, reasons youth would likely get tested, willingness to use school‐based sexual health services, and youth preferences for how sexual health services should be provided in schools. Other aspects of the data collection are reported in elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…More specifically, the US Centers for Disease Control and Prevention (CDC) recommends that MSM are tested for HIV and other STDs at least annually. 7,8 To address the needs of teen black and Hispanic YMSM as they begin engaging in sexual risk behaviors, the CDC's Division of Adolescent and School Health is developing a school-centered project for YMSM aged [13][14][15][16][17][18][19]. Because the majority of high-school aged youth have not begun engaging in sexual activity, 9 YMSM is defined broadly for this project to include: males who have engaged in same-sex sexual activity as well as those who may not have engaged in same-sex sexual activity, but who identify as gay or bisexual, or who report attraction to other males.…”
mentioning
confidence: 99%
“…Slater et al (2015) To determine predictors of homonegativity, internalized HIV stigma, and ageism and stigma experience that were predictive of quality of life setting appointments to see a doctor and a large private hospital denied in vitro fertilisation/donor insemination (IVF/DI) to lesbian couples. However, the situation was later rectified after the couple concerned threatened potential legal action (Chapman, Wardrop, Freeman, et al, 2012).In the United States, black and Latino young men who have sex with men revealed a reluctance to talk to nursing staff when they were uncertain of the staff members' perceptions of LGB people or when they perceived that staff lacked knowledge of LGB issues (Rasberry et al, 2015).…”
Section: Shields Et Al (2012)mentioning
confidence: 99%